Nucleus Pulposus Replacement: Hydrogel or Scaffold?—An Organ Culture Study under Dynamic Load. (May 2014) - Li, Z.; Chen, X.; Sacks, H.; Yayon, A.; Alini, M.; Grad, S.
Introduction: Nucleus pulposus (NP) replacement offers a minimally invasive disc regeneration treatment alternative to traditional fusion or total disc replacement. An ideal NP replacement material should maintain motion and disc height, thus slowing down further disc degeneration. 1 Various biomaterials have been investigated for their use as NP replacement, including hydrogel and nonhydrogel scaffolds, while no direct comparison study has been performed. Recently, a novel fibrin-hyaluronan (FBG-HA) conjugate hydrogel was developed to mimic native NP extracellular matrix. In addition, a novel polyurethane (PU) scaffold with swelling capability in situ was designed to restore native disc thickness and mechanical properties. The present study aimed to assess the FBG-HA hydrogel, the PU scaffold, and the combination of both in an organ culture system with dynamic load for the purpose of NP replacement. Materials and Methods: FBG-HA conjugate solution was synthesized with 235 KDa HA at FBG/HA w/w ratio of 17:1 via a two-step procedure as described elsewhere. 2 FBG-HA hydrogels were prepared by mixing two-thirds volume of FBG-HA conjugate solution with one-third volume of thrombin solution (5.2 U/mL) and allowed to polymerize at 37°C for 20 minutes. The PU scaffold was designed to have a flat discoid/ravioli shape that is composed of a based core with swelling capacity. Electrospinning nanofibers technology was used to manufacture an envelope sheet using a blend of polyurethane carbonates (ChronoFlex and HydroMed) that were dissolved in a mixture of dimethylformamide and dioxane. The envelope was cut to discs at diameter of 6 mm. The PU hydroMed was dissolved in 95% ethanol and dried to form a film. The film was cut to discs at diameter of 3 mm. One film disc was placed between two envelope discs and the circumference was heat welded to form a scaffold with ravioli shape. Caudal bovine intervertebral discs (IVDs) with endplates were obtained from calves (4-8 months) directly after slaughter. The discs were nucleotomized by incisions through the endplate. A 4-mm endplate core and the NP tissue below the endplate stopper were removed. The nucleotomized region was refilled with either (1) 50 to 80 µL FBG-HA hydrogel, (2) dry PU scaffold, or (3) PU scaffold surrounded by FBG-HA hydrogel. To close the defect, the removed endplate stopper was re-inserted, and the crack between the stopper and the remaining endplate was sealed by polymethyl methacrylate. Empty discs served as negative controls. To assess the mechanical compatibility of the different biomaterial implants, dynamic compressive stiffness modulus and disc height were measured for each disc at different time points: Intact, after nucleotomy, after refilling with biomaterial and free swelling culture overnight, after 3 hours dynamic load at 0 to 0.1 MPa, 0.1 Hz within a bioreactor system, 3 and after free swelling recovery overnight. Results: Dry PU scaffold was able to trap water and swell in situ already after 24 hours culture in the disc, as indicated by weight increase of 301 ± 33% and thickness increase of 103 ± 15%. Addition of FBG-HA hydrogel did not affect the swelling capability of the PU scaffold. After nucleotomy, the dynamic compressive stiffness modulus dropped to 30%. After refilling the NP cavity with PU scaffold and free swelling culture overnight, the disc stiffness modulus was restored to 73 ± 21% ( p < 0.05 vs. control). After 3 hours dynamic load and overnight free swelling recovery, the stiffness modulus of PU scaffold refilled discs further increased to 82 ± 14% ( p < 0.01 vs. control). Addition of FBG-HA hydrogel surrounding the PU scaffold delayed the stiffness restoration effect, while after 3 hours dynamic load and overnight free swelling recovery the stiffness also increased to 69 ± 16% ( p < 0.05 vs. control) (Fig. 1A). After dissection and overnight culture, disc height increased by 2.6 to 4.5% due to swelling. Nucleotomy caused 3% decrease in disc height. Refilling the NP cavity with biomaterial did not change the disc height. However, after 3 hours dynamic load, all the three implant groups showed significantly higher disc height compared with empty discs ( p < 0.001). After free swelling recovery overnight, the disc heights of all groups recovered ( p < 0.001 implanted vs. control) (Fig. 1B). Conclusion: Results indicate that PU scaffold may be a superior NP replacement material in terms of mechanical property repair compared with FBG-HA hydrogel. While combination of PU scaffold and FBG-HA hydrogel might result in better biological repair of NP, as FBG-HA hydrogel mimics native NP extracellular matrix and is a good carrier for cells implantation and/or drug delivery. Long-term study with the current well-established organ culture model will be performed to investigate the biological effect of PU scaffold, combined with FBG-HA hydrogel for NP replacement. Disclosure of Interest Z. Li: Conflict with the European Commission under the FP7 - NMP Project NPmimetic X. Chen: Conflict with the European Commission under the FP7 - NMP Project NPmimetic H. Sacks: Conflict with the European Commission under the FP7 - NMP Project NPmimetic; Conflict with Nicast Ltd A. Yayon: Conflict with the European Commission under the FP7 - NMP Project NPmimetic; Conflict with Procore Laboratories M. Alini: Conflict with the European Commission under the FP7 - NMP Project NPmimetic S. Grad: Conflict with the European Commission under the FP7 - NMP Project NPmimetic References Coric D, Mummaneni PV. Nucleus replacement technologies. J Neurosurg Spine 2008;8(2):115–120 Amit B, Barkay-Olami H, Yayon A. Water soluble reactive derivatives of carboxy polysaccharides and fibrinogen conjugates thereof. US patent 8, 329, 870, CIP US 13/685150 EP 2106263; India patent 4691/DELNP/2009 A. February 26, 2010 Jünger S, Gantenbein-Ritter B, Lezuo P, Alini M, Ferguson SJ, Ito K. Effect of limited nutrition on in situ intervertebral disc cells under simulated-physiological loading. Spine 2009;34(12):1264–1271